2017
DOI: 10.18203/2320-1770.ijrcog20175028
|View full text |Cite
|
Sign up to set email alerts
|

Study of perinatal outcome in twin gestation in rural referral hospital in Maharashtra (India): a cross sectional study

Abstract: Background: Incidence of twin pregnancy is increasing all over the world. It can occur after Assisted Reproductive Technology (ART) or spontaneously and associated with increased maternal and neonatal complications both in the developed and developing countries.Methods: A descriptive (Cross sectional) study of 64 cases of twins was undertaken between January 2013 till December 2015. Data collection was done prospectively from the patients admitted to the hospital with twin gestation. Inclusion criteria: All pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Other studies also reported higher incidence of obstetrical complications with multifoetal pregnancies with preterm labour and anemia were common complications. 13 Figure 2 shows majority of monochorionic and trichorionic gestations were delivered before 34 weeks whereas dichorionic gestations were delivered after 34 weeks. A study by Assuncao et al reported similar observation where most deliveries in monochorionic pregnancies took place at 31-33 weeks and in dichorionic pregnancies at 34-36 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported higher incidence of obstetrical complications with multifoetal pregnancies with preterm labour and anemia were common complications. 13 Figure 2 shows majority of monochorionic and trichorionic gestations were delivered before 34 weeks whereas dichorionic gestations were delivered after 34 weeks. A study by Assuncao et al reported similar observation where most deliveries in monochorionic pregnancies took place at 31-33 weeks and in dichorionic pregnancies at 34-36 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%